7x-9x+6=-4x+6

Simple and best practice solution for 7x-9x+6=-4x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-9x+6=-4x+6 equation:


Simplifying
7x + -9x + 6 = -4x + 6

Reorder the terms:
6 + 7x + -9x = -4x + 6

Combine like terms: 7x + -9x = -2x
6 + -2x = -4x + 6

Reorder the terms:
6 + -2x = 6 + -4x

Add '-6' to each side of the equation.
6 + -6 + -2x = 6 + -6 + -4x

Combine like terms: 6 + -6 = 0
0 + -2x = 6 + -6 + -4x
-2x = 6 + -6 + -4x

Combine like terms: 6 + -6 = 0
-2x = 0 + -4x
-2x = -4x

Solving
-2x = -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-2x + 4x = -4x + 4x

Combine like terms: -2x + 4x = 2x
2x = -4x + 4x

Combine like terms: -4x + 4x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 2a+6b+18c= | | 4/9(18w-36)-2/9(9w/2-9)=0 | | 5(x-1)=3(x+9) | | 32r-80z= | | 30m-120= | | s-15=-33 | | 24v+32w= | | 9p+21= | | 3x+2+5x-5=25 | | 6x+2y+6=0 | | 12x+8=10x+40 | | 10x^3+8x^2+2x=0 | | 9x+6-10x-25=30 | | 12n+2=4n+3 | | -3x+4=(-2)x+(-19) | | 4f-24g= | | 4+12/x=7 | | 12n+5=4n+6 | | -27-3x=6x+24 | | -81-9x=21+8x | | 10r-15s= | | 12n+3=4n-6 | | 9x^2-79x-130=0 | | 14c+28d= | | 7y+6x-3=3y-3x+2 | | n+(-20)=7-n | | 84-3x=3x+24 | | 4y+6z= | | 35-3x=2x | | 61-3x=61-3x | | 8n+24= | | 5e-5f= |

Equations solver categories